Editorial - Alberca-Sialer, Fabrizio Augusto (2025)
The journal Turismo y Patrimonio celebrates 25 years since its first publication. Over this quarter of a century, the journal has undergone significant changes. Among the most notable are the transition from an annual periodicity (sometimes with longer intervals) to a semiannual one, the regular strengthening of the editorial team, the implementation of blind peer review, and the exclusive publication in digital format. The cover design has also changed more than once during this time, as has the layout of the texts on its pages. All these changes, it should be noted, have been positive.